Gonadal development in pejerrey (Odontesthes bonariensis) during spawning season in relation with sex steroids and temperature variation in gómez lake (Pampas region, Argentina) - del Fresno, Pamela Sabrina (2021)
Gómez lake (34 ° 39 ‘S 61 ° 01’ W) is a typical shallow lake of Pampas region placed in the upper area of the Salado river. The most abundant fi sh species in this lake is the pejerrey (Odontesthes bonariensis) valued due to the quality of its fl esh and its attractiveness as a game fi sh. The aim of this study was to describe for the fi rst time in this pejerrey wild population the gonadal stages during three consecutive spawning seasons (August to December) in relation with sexual steroids and temperature in this lake. In general, pejerrey gonadal development, the gonadosomatic index and the plasma levels of estradiol and testosterone varied in relation to air t emperature. During the sampling period, pejerrey females started to ovulate in early August (winter), with a peak in October and ending in December with some of them with atretic oocytes. For males, it was possible to fi nd spermiating animals during the whole spawning season and some arrested animals only in December. Our results confi rm the relationship with pejerrey maturation and temperature and can be useful for decision making in the management of this natural resource.